Extended reality and informative models for the architectural heritage: from scan-to-BIM process to virtual and augmented reality - Fabrizio Banfi; Raffaella Brumana; Chiara Stanga (Virtual Archaeology Review)
The dissemination of the tangible and intangible values of heritage building represents one of the most important objectives in the field of Digital Cultural Heritage (DCH). In recent years, different studies and research applied to heritage monuments have shown how it is possible to improve the awareness of the architectural heritage through the integration of latest developments in the field of 3D survey, 3D modelling, Building Information Modeling (BIM) and eXtended Reality (XR). On the other hand, this digital workflow requires a huge amount of data sources and a holistic approach to reach a high level of information sharing coming from different disciplines and sectors such as restoration, geomatics, 3D virtual museums and serious gaming. In conjunction with entertainment software and gaming, this research shows the main results obtained during the generative process of digital environments oriented to improve the level of information and to enrich the contents coming from the informative models. The case study is represented by one of the most important Lombard monuments: the Basilica of Sant’Ambrogio in Milan. This study, starting from the 3D survey and the data collection of the historical records of the church, improves the creation of an XR experience that reaches a new level of interactivity for different types of devices (desktop, mobile, VR headset) and users (experts, non-experts).